Metagenome-mining indicates an association between bacteriocin presence and strain diversity in the infant gut - Ida Ormaasen; Knut Rudi; Dzung B. Diep; Lars Snipen (BMC Genomics, 2023)
Abstract Background Our knowledge about the ecological role of bacterial antimicrobial peptides (bacteriocins) in the human gut is limited, particularly in relation to their role in the diversification of the gut microbiota during early life. The aim of this paper was therefore to address associations between bacteriocins and bacterial diversity in the human gut microbiota. To investigate this, we did an extensive screening of 2564 healthy human gut metagenomes for the presence of predicted bacteriocin-encoding genes, comparing bacteriocin gene presence to strain diversity and age. Results We found that the abundance of bacteriocin genes was significantly higher in infant-like metagenomes (< 2 years) compared to adult-like metagenomes (2–107 years). By comparing infant-like metagenomes with and without a given bacteriocin, we found that bacteriocin presence was associated with increased strain diversities. Conclusions Our findings indicate that bacteriocins may play a role in the strain diversification during the infant gut microbiota establishment.